(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
The culture of speech consists in solving all kinds of speech exercises from a practical point of view. Therefore, in the science of the culture of speech, there is an opinion about patterns, secrets, language, language norms, words, characteristics of words, styles of speech, errors and defects that can occur in speech, speech norms, exercises related to the pronunciation of words